Peran Perpustakaan Digital dalam Meningkatkan Minat Baca Mahasiswa di Era Transformasi Digital - Wahidi, Ahmad; Azkia, Corry (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Advancements in information technology have brought about significant changes across various aspects of life, including the realm of education. One manifestation of this technological integration is the emergence of digital libraries, which enable users to access diverse information resources quickly, easily, and flexibly. This study aims to examine the role of digital libraries in fostering students' interest in reading during the era of digital transformation. A library research method employing a qualitative descriptive approach was utilized. Data were gathered through a review of relevant scholarly sources, such as journals, books, and research articles. The findings indicate that digital libraries contribute positively to enhancing students' reading interest by providing easy access to information, a diverse range of digital collections, effective search tools, and support for independent learning. Furthermore, digital libraries play a role in improving students' digital literacy and expanding access to scholarly resources. However, challenges remain, such as limited internet access, varying levels of digital literacy among users, and copyright issues. Consequently, infrastructure support and the enhancement of user competencies are essential to ensure the optimal utilization of digital libraries.